Decoding the silent walk of COVID-19: Halting its spread using old bullets (2020)
Severe acute respiratory syndrome (SARS) develops within 3-14 days when CoV2 invades epithelial, myeloid cells in the nasopharynx and pneumocytes in the respiratory tract through angiotensin converting enzyme (ACE2). Infection swiftly disseminates to gastrointestinal, cardiovascular, renal organs as well as immune system to deregulate their normal functioning through unique and distinct mechanisms. The health system and economy has been intensely thwarted by the rapid spread and exorbitant mortality caused by COVID-19 disease across the globe. The acute progression of the disease and high infection rate pose an enormous challenge for its therapeutic management and critical care. The viral structure, genome and proteome have been deciphered which yielded cues for targeting already available therapeutic entities. More than 200 compounds have been screened and till date approximately 69 therapeutic agents are undergoing clinical trials across the world. Among these, remedesivir (RMD), chloroquine (CQ), hydroxychloroquine (HCQ), noscapine (NOS) and heparin have demonstrated fairly promising results in preclinical and clinical studies. Recently, RMD has been approved by USFDA for the management of COVID 19. However, intense research is going on to screen and ace the ‘magic bullets’ for the management of SARS-CoV2 infection worldwide. The current review illustrates the plausible therapeutic targets in SARS-CoV2 important for inhibition of virus cycle. In addition, the role of RMD, CQ, HCQ, NOS and heparin in combating infection has been addressed. The importance of vitamin C and D supplements as adjunct therapies in the prevention of SARS-CoV2 virus infection have also been summarized.